RANCANGAN PEMBUATAN APLIKASI PRESENSI DENGAN SIDIK JARI - Irvin Jefferson; Bobby Tumbelaka (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Student attendance application with fingerprints is designed to improve efficiency in the attendance of students, lecturers and assistant lecturers. This application is web-based and built using the PHP programming with laravel framework. This application is made to prevent manipulation of attendance data done by the students, an error copying the data by the academic and attendance data completeness cause confusion during the making recap attendance by the academic authorities. Therefore, we need a system that is able to overcome the problem of absenteeism is done manually, by using fingerprints as a means to confirm their attendance. Fingerprints are one of the unique characteristics of a person where each student has different fingerprints with the other students. From the results of the evaluation of this application can be concluded that this application provides the benefits of avoiding the manipulation of data, save time to confirm their attendance and facilitate the academic authorities in the manufacture recap attendance.